Draft Genome Sequence of a Novel SAR11 Clade Species Abundant in a Tibetan Lake - Oh, Seungdae (Genome Announc, 2014)
SAR11 clade bacteria are abundant and play a key role in the nutrient cycles of marine and, presumably, inland aquatic environments. We report here the draft genome sequence of a novel species in the SAR11 cluster, reconstructed from a metagenomic data set obtained from a Tibetan lake.